Study on La2(Hf1-xTix)2O7 (x ≤ 0.20) pyrochlores for potential thermal/environmental barrier coating applications. Issue 22 (15th November 2022) - Du, Jinping; Liu, Rongjun; Wan, Fan; Li, Duan; Li, Junsheng; Wang, Yanfei
Abstract: Lanthanum hafnate (La2 Hf2 O7 ) with a pyrochlore structure has excellent high temperature stability and low thermal conductivity, which is promising for thermal/environmental barrier coatings (T/EBCs) applications. To reduce its thermal expansion coefficient (TEC) so as to better match SiCf /SiC composites, a smaller tetravalent dopant Ti 4+ has been introduced in the Hf-sites to form La2 (Hf1-x Tix )2 O7 (x ≤ 0.20). The phase composition and microstructure confirms that La2 (Hf1-x Tix )2 O7 solid solutions possess a pure pyrochlore structure. With an increase of x, their TECs are decreasing consistently, whilst their thermal conductivities of La2 (Hf1-x Tix )2 O7 are slightly increasing at high temperature but still much lower than those of meta-stable yttria partially stabilized zirconia, both of which are attributing to an increase of elastic modulus after Ti 4+ doping on Hf-sites. The extremely excellent high temperature stability, relatively low thermal conductivities and low TECs suggest that La2 (Hf1-x Tix )2 O7 is a prospective candidate material for T/EBC applications.